Traditional beluga drives of the Iñupiat of Kotzebue Sound, Alaska / Fieldiana, Anthropology, new series, no.25 - Lucier, Charles V.; VanStone, James W.; Field Museum of Natural History. (Chicago : Field Museum of Natural History, 1995)
Includes bibliographical references (p. 89-91). Fieldiana series has been published as Anthropological Series by Field Columbian Museum (1895-1909) and Field Museum of Natural History (1909-1943), and as Fieldiana: Anthropology by Chicago Natural History Museum (1945-1966) and Field Museum of Natural History (1966-).